Impact of Sorting Machine on Life Cycle of Passive UHF RFID Tags Placed on Letter Mail - Kolarovszki, Peter; Tengler, Jiri; Perakovic, Dragan; Perisa, Marko (Communications - Scientific letters of the University of Zilina, 2018)
This article deals with research of passive RFID technology in conjunction with letter-size mail, which is placed into sorting machine. RFID technology is a part of automatic identification and data capture. In this article we would like to describe an identification of letter mail based on passive technology. We would like to specify, how the sorting machine impacts a readability of RFID tags placed on letter mail. We have established a number of variants of placing RFID tags into envelopes. After passing these tags, we evaluated their readability. Then we compared the results before and after passing the letters through the sorting line. All results are verified by measurement at the Slovak post main processing center located in Zilina. The results of our research bring the new point of view and indicate the ways of using of UHF RFID technology in postal and logistics applications. At the end of this article we evaluate the impact of the selected sorting line on a life cycle of RFID tags.